Eating attitudes and depressive symptoms in a LGBTIQ sample in Turkey - Güleç, Hayriye; Torun, Tayfun; Prado, Aneliana da Silva; Bauer, Stephanie; Rummel-Kluge, Christine; Kohls, Elisabeth (Frontiers in psychology, 2022)
Lesbian, gay, bisexual, transgender, intersexual and queer (LGBTIQ) individuals are often stigmatized due to their minority status. Sexual-minority stress is often discussed as a risk factor for the increased mental health problems reported in this population. The current study (1) investigated eating attitudes and depressive symptoms in a sexual minority sample from Turkey who identify themselves as LGBTIQ and (2) explored the role of sexual minority stressors beyond the potential predictors of eating attitudes and depressive symptoms in this population.